Photophysical properties and bisulfite recognition of a coumarin cyanopyridine derivative. (November 2020) - Ma, Shuyue; Wang, Kangnan; Yu, Xuelai; Zhang, Yixin; Xing, Miaomiao; Wu, Xiangwen; Cao, Duxia; Liu, Zhiqiang
Abstract: A coumarin cyanopyridine derivative 1 (3-(7-diethylamino-2-oxo-2H-chromen-3-yl)-2-pyridin-4-yl-acrylonitrile) was developed as bisulfite fluorescence chemosensor. Two different crystals 1 a (blue block, triclinic system, P-1 space group) and 1 b (red plate, monoclinic, P 21 /n space group) were obtained from acetonitrile (1 a ) and dichloromethane (1 b ), respectively, by slow solvent evaporation. The probe emits strong blue fluorescence emission (468 nm, 482 nm) and high fluorescence quantum yield (0.22) in hexane. Fluorescent peak of the probe exhibits linear relationship to solvent polarity with high linear correlation coefficient and then can track environmental polarity. The probe can recognize bisulfite (HSO3 − ) in HEPES solution with blue fluorescence (485 nm) enhancement response and low detection limit being 1.02 nM, which has high sensitivity compared with other chemosensors for HSO3 − reported in references. The mechanism analysis by in situ 1 H NMR and mass spectrum indicates that HSO3 − is added to the CC bond and the broken charge transfer from diethylcoumarin to pyridine group leads the strong blue fluorescence appearance from coumarin. The probe also has the potential application in monitoring HSO3 − in living cells. Graphical abstract: Image 1 Highlights: A bisulfite probe based on coumarin cyanopyridine skeleton was developed. Two kinds of crystals of the probe were obtained from CH2 Cl2 and CH3 CN, respectively. Fluorescent peak wavelength of the probe can track environmental polarity. The probe can sense HSO3 − with fluorescence turn-on and low detection limit (1.02 nM).